2010
DOI: 10.1063/1.3359655
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical, structural, and mechanical properties of Si3N4 films annealed in O2

Abstract: The physicochemical, structural, and mechanical properties of silicon nitride films deposited by radio frequency reactive magnetron sputtering were investigated before and after thermal annealing in 18 O 2 . As-deposited films were essentially amorphous, stoichiometric, and free from contaminants for a wide range of deposition parameters, with hardness figures ranging from 16.5-22 GPa, depending mainly on the deposition temperature. After 18 O 2 annealing at 1000°C, films hardness converged to 21 GPa, independ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Indeed, binding energy for the observed N1 s peak was in good agreement with nitride ion in typical nitrides and shift of Si2 p peak according to nitrogen insertion was obviously seen. As Si2 p states were found to be intermediate states between that of SiO 2 and Si 3 N 4 , 31‐34 we can safely conclude that the aerogels transformed to oxynitride, a‐Si(O,N) x , by ammonolysis. However, quantitative analysis could not be achieved by XPS, because serious charging caused obvious reduction of spectral intensity particularly for the sample after ammonolysis at higher temperature and presence of adsorbates, for example, –OH, caused difficulty in accurate determination of oxygen‐related peak intensities.…”
Section: Resultsmentioning
confidence: 70%
“…Indeed, binding energy for the observed N1 s peak was in good agreement with nitride ion in typical nitrides and shift of Si2 p peak according to nitrogen insertion was obviously seen. As Si2 p states were found to be intermediate states between that of SiO 2 and Si 3 N 4 , 31‐34 we can safely conclude that the aerogels transformed to oxynitride, a‐Si(O,N) x , by ammonolysis. However, quantitative analysis could not be achieved by XPS, because serious charging caused obvious reduction of spectral intensity particularly for the sample after ammonolysis at higher temperature and presence of adsorbates, for example, –OH, caused difficulty in accurate determination of oxygen‐related peak intensities.…”
Section: Resultsmentioning
confidence: 70%
“…Metal–dielectric composite (cermets)-based SSACs have been widely investigated in terms of their great optical performance and thermal stability. As an essential component of the SSAC, the selection of the ceramic matrix would have a crucial impact on the optical performance and thermal stability of the coatings . It has been shown that silicon nitride exhibits excellent mechanical properties, thermal stability, corrosion resistance, and oxidation resistance at high temperatures. Hence, silicon nitride is a promising ceramic matrix candidate for high-temperature SSACs. The Mo–Si 3 N 4 -based SSAC showed a high solar absorptivity (α sol = 0.926) and a low emissivity (ε 600°C = 0.109).…”
Section: Introductionmentioning
confidence: 99%